Scrutinising Eurocentric stereotypes against Afrocentric underpinnings of beauty through Kopano Matlwa’s Coconut (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This paper has probed into stereotypical attitudes towards Afrocentric underpinnings of beauty through Kopano Matlwa’s Coconut. The genesis of these stereotypes against African beauty could be traced from the colonisation of the African continent. It is the interface between Africa and the West that engendered a shift of identities, which resulted in many Afrocentric depictions assimilated d by Western influence. Despite the decolonisation attempts, the Eurocentric notions that had defined Africa during the colonial period persist in galvanising stereotypes that marginalise Africans, especially those that embrace Afrocentric ideas of beauty in the post-colonial age. Today, Africa is besieged with remnants of colonialism, which include Eurocentric ideals of beauty. This paper employed the qualitative method to scrutinise the stereotypes against Afrocentric beauty through the literary criticism of Matlwa’s novel, Coconut. It is undergirded by the theory of Afrocentricity, which has been utilised as a lens to crystalise the indigenous African identities and their relevance today. It finds that these Eurocentric notions have navigated through the peripheries of post-colonial Africa and influenced societal reactions, attitudes and perceptions of beauty. This is reflected in Matlwa’s Coconut where African beauty is stigmatised and disparaged whereas Eurocentric ideals of beauty are exalted.